The economics of freedom theory, measurement, and policy implications - Bavetta, Sebastiano 1964-; Navarra, Pietro; Cambridge Books Online (Online service). (Cambridge Cambridge University Press, 2012)
"What is freedom? Canwemeasure it? Does it affect policy? This book develops an original measure of freedom called autonomy freedom, consistent with J. S. Mill's view of autonomy, and applies it to issues in policy and political design. The work pursues three aims. First, it extends classical liberalism beyond exclusive reliance on negative freedom so as to take autonomous behavior explicitly into account. Second, it is grounded on firm conceptual foundations a new standard in the measurement of freedom that can be fruitfully coupled with existing gauges. Third, it shows empirically that individual preferences for redistribution and cross-country differences in welfare spending in Organisation for Economic Cooperation and Development (OECD) countries are driven by the degree of autonomy freedom that individuals enjoy. By means of an interdisciplinary approach and a sophisticated econometric methodology, the book takes an explicit stand in defense of freedom and sets the basis for a liberalism based upon people, actions, and institution"-- Provided by publisher
1. Introduction; Part I. Concepts and Tools: 2. Choice and freedom; 3. Measuring autonomy freedom; 4. The empirical measure of autonomy; Part II. Autonomy Freedom and the Welfare State: 5. Why redistribute?; 6. Autonomy freedom and redistribution; 7. Autonomy freedom and welfare spending; 8. Conclusion
Title from title screen (viewed on November 7, 2023)
Also issued in print format
Mode of access: World Wide Web
Keywords: Economics -- Political aspects; Liberty -- Economic aspects; Autonomy -- Economic aspects